Use of flow cytometry in the diagnosis of lymphoproliferative disorders in fluid specimens. Issue 8 (19th February 2014) - Yu, Gordon H.; Vergara, Norge; Moore, Erika M.; King, Rebecca L.
<x xml:space="preserve">Abstract</x> The diagnostic evaluation of fluid specimens, including serous effusions and cerebrospinal fluids (CSFs), can be challenging for a number of reasons. The evaluation of lymphoid proliferations in these specimens can be particularly problematic, given the frequent presence of coexisting inflammatory conditions and the manner in which these specimens are processed. As a result, immunophenotypic analysis of hematopoietic cell populations by flow cytometry has emerged as a useful ancillary study in the diagnosis of these specimens, both in patients with and without a previous history of a lymphoproliferative disorder. In this study, we review our experience with flow cytometry in fluid specimens over a four‐year period. Flow cytometry was performed in 184 of 6, 925 total cases (2.7% of all fluids). Flow cytometry was performed in 4.8% of pleural fluids (positive findings in 38%, negative in 40%, and atypical in 18%), 1.1% of peritoneal fluids (positive in 40%, negative in 50%, and atypical in 10%), 1.9% of pericardial fluids (positive in 67%, negative in 33%), and 1.9% of CSFs (positive in 23%, negative in 55%, atypical in 3%). The specimen submitted was inadequate for analysis in 9.2% of cases, most commonly with CSF specimens, but was not related to the volume of fluid submitted. Atypical flow cytometry findings and atypical morphologic findings in the context of negative flow cytometry results led to the definitive diagnosis of a lymphoproliferative disorder in a significant number of cases when repeat procedures and ancillary studies were performed. Diagn. Cytopathol. 2014;42:664–670. © 2014 Wiley Periodicals, Inc.